Chapter Quero uma rua de Roma. Scrittori portoghesi in viaggio a Roma - Trognoni, Claudio (Studi e saggi, 2021)
Since its independence, Portugal had strong commercial, political, and cultural ties with the Italian Peninsula. This place has always been a source of inspiration for writers and artists from all over the world: throughout the centuries, Rome has been able to attract a considerable number of Portuguese authors, who, from time to time, have approached the city or as the cradle of Catholicism, or as a place where they can revive their own Latin and classical roots. This article aims to highlight how Rome has been able to inspire Portuguese authors travelling through the city, in an attempt to highlight, isolate and describe the common elements existing among them.